Ciberacoso e violência de gênero: uma perspectiva linguística sobre stalkers seriais - Benedetti, Novella (2025)
Cyberstalking is a growing form of gender-based violence characterized by linguistic manipulation, coercion, and threats. This study analyzes messages sent by the same perpetrator to two different victims, aiming to identify recurring linguistic patterns and assess potential escalation dynamics in verbal violence. Through a quantitative and qualitative analysis of digital conversations, three main dimensions are examined: discursive domination and narrative control, personal devaluation, and the use of offensive and degrading language. The objectives are: to verify whether the serial aggressor reproduces the same linguistic strategies; to detect potential increases in the intensity of violence; and to describe how these changes manifest. The findings provide deeper insight into recidivism in cyberstalking cases and reinforce the current relevance of forensic linguistics as key expert evidence in the prosecution of online gender-based violence.